Laser powder bed fusion of Mg–Zn–Zr alloy: Formability, microstructure evolution and biodegradation behavior - Youwen Yang; Jiapeng Ren; Cheng Chen; Yinjin Shao; Xiong Shuai; Xuehua Wu; Chunrong Pan; Cijun Shuai (Journal of Materials Research and Technology)
Laser powder bed fusion (LPBF) was used to fabricate Mg–Zn–Zr (ZK60) parts, with a thorough investigation of processability by varying laser power and scanning rate. The combined effect of these parameters, which determines laser energy density, significantly impacted the forming quality of LPBF ZK60. Dense parts (over 99%) free of visible defects such as pores and cracks were achieved at a laser energy density of 74.1 J/mm2. The formation mechanisms of pores and cracks were extensively analyzed concerning the characteristics of the molten pool and subsequent cooling behavior. The LPBF ZK60 parts exhibited extremely fine grains, with an average grain size of 3.2 μm. Both equiaxed and columnar grains were observed, with a central equiaxed zone in the melt pool and a perpendicular lamellar zone along its boundary. Additionally, the Mg7Zn3 eutectic phase precipitated within the α-Mg matrix of ZK60. Immersion and electrochemical tests indicated that the XZ plane displayed superior corrosion resistance, attributed to fewer deformation regions and lower dislocation density. Furthermore, in vitro cell experiments confirmed that the ZK60 alloy possesses good biocompatibility.